The Patterns of Human Trafficking of Indonesian Migrant Workers: Case Study of the Riau Islands and Johor Border Crossing - Sulaksono, Endro (Masyarakat: Jurnal Sosiologi, 2018)
In this article, patterns of sending Indonesian migrant workers through the cross-border between the Riau Islands, Indonesia and Johor, Malaysia are examined. These patterns have implications for transnational crimes of human smuggling and trafficking. A new pattern involving Indonesian migrant workers was revealed. The migrant workers enter and reside in the destination country legally and subsequently become illegal migrants because the employer or the company does not extend their contracts. This pattern differs from two other patterns that are commonly practiced and are well-known: legal entry and illegal stay, if migrant workers work in a destination country without working permits; and illegal entry and illegal stay, if migrant workers enter a destination country through illegal mediums and work there without valid documents. This finding enriches previous studies on patterns involved in people smuggling and human trafficking with emphasizes that Indonesian migrant workers’ vulnerability cannot be reduced to mere proceduralbureaucratic matters. This research employed the case study method. The primary data was collected by conducting in-depth interviews with Indonesian migrant workers who became victims of human trafficking as key informants.